Lactobacillus plantarum KAD protects against high-fat diet-induced hepatic complications in Swiss albino mice: Role of inflammation and gut integrity. - Supriyo Ghosh; Amlan Jyoti Ghosh; Rejuan Islam; Sagar Sarkar; Tilak Saha (PLoS ONE)
Hepatic complications are the major health issues associated with dietary intake of calorie saturated food e.g. high-fat diet (HFD). Recent studies have revealed the beneficial effects of probiotics in HFD fed mice with hepatic complications. Some probiotic Lactic acid bacteria (LAB) e.g. Lactobacillus plantarum have drawn our attention in managing hepatic complications. Here, we aim to elucidate the protective effects of L. plantarum KAD strain, isolated from ethnic fermented food 'Kinema' in HFD-fed mice as, a preventive approach. Eighteen Swiss albino mice were equally divided into 3 groups: Normal Diet (ND), negative control (HFD), and HFD-fed with oral L. plantarum KAD supplementation (LP). All the experimental groups were subjected to specific diet according to grouping for eight weeks. After completion of the regime, subjects were anesthetized and sacrificed. Organs, blood, and fecal samples were collected and stored appropriately. Physical indices, including body weight gain, organ co-efficients were calculated along with assessment of glycemic, lipidomic, hepatic, oxidative stress, inflammatory, and histological parameters. Gut microbiota analysis was performed using 16s V3-V4 fecal metagenomic profiling, and sequencing were done using Illumina Miseq system. Oral administration of L. plantarum KAD is found to significantly (p<0.05) restore metabolic health by normalizing glycemic, lipidomic, hepatic parameters, oxidative stress and inflammatory parameters. Moreover, LP group (7.08±0.52 mg/g) showed significantly (p<0.001) decreased hepatic triglyceride level compared to HFD group (20.07±1.32 mg/g). L. plantarum KAD improved the adipocytic, and colonic histomorphology with significantly better scoring pattern. LP group (1.83±0.41) showed a significantly (p<0.001) reduced hepatic score compared to negative control group (5.00±0.63), showing reduced hepatosteatosis, and immune infiltration. The strain modulated gut health by altering its microbial composition positively towards normalization. In conclusion, the results of the experiment suggest that prophylactic L. plantarum KAD administration has beneficial effects on the onset of HFD induced hepatic complications in mice. Further studies are needed, on this strain for its clinical use as dietary supplement.